2022
DOI: 10.1021/acs.jmedchem.2c01058
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel G-Quadruplex and Histone Deacetylase (HDAC) Dual-Targeting Agent for the Treatment of Triple-Negative Breast Cancer

Abstract: The development of triple-negative breast cancer (TNBC) is highly associated with G-quadruplex (G4); thus, targeting G4 is a potential strategy for TNBC therapy. Because concomitant histone deacetylases (HDAC) inhibition could amplify the impact of G4-targeting compounds, we designed and synthesized two novel series of G4/HDAC dual-targeting compounds by connecting the zinc-binding pharmacophore of HDAC inhibitors to the G4-targeting isaindigotone scaffold (1). Among the new compounds, a6 with the potent HDAC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 71 publications
(138 reference statements)
0
2
0
Order By: Relevance
“…The related clinical trial is ongoing, with results to be announced. In addition, Jiang et al found that compound A6, which targets both HDAC and G-quadruplex (G4), significantly inhibited the proliferation of TNBC cells and demonstrated a favorable safety profile in a mouse model [ 165 ]. Moreover, the combination of HDAC inhibitors and ionizing radiation may benefit patients with TNBC [ 166 ].…”
Section: Tnbc-related Targeted Therapymentioning
confidence: 99%
“…The related clinical trial is ongoing, with results to be announced. In addition, Jiang et al found that compound A6, which targets both HDAC and G-quadruplex (G4), significantly inhibited the proliferation of TNBC cells and demonstrated a favorable safety profile in a mouse model [ 165 ]. Moreover, the combination of HDAC inhibitors and ionizing radiation may benefit patients with TNBC [ 166 ].…”
Section: Tnbc-related Targeted Therapymentioning
confidence: 99%
“…Histone deacetylases (HDACs) are an important component of epigenetic factors to catalyze the removal of acetyl and acyl groups from the modified ε-amino moiety of lysine in histone tails, thereby playing an essential role in the regulation of target gene expression. , The dysregulation of HDAC expression has been implicated in various cancer types, making HDACs attractive targets for cancer therapy. Correspondingly, there were many endeavors that contributed to the development of HDAC inhibitors (HDACis) as a new therapeutic treatment, including pan-HDACis, subtype-selective HDACiss, and dual-target inhibitors based on HDAC. Notably, five HDACis, namely, vorinostat (SAHA), belinostat, panobinostat, romidepsin, and chidamide, have been approved for the treatment of T-cell lymphoma and multiple myeloma (Figure ). Besides, several HDACis have been launched in clinical trials; for instance, abexinostat was in the phase III stage of a clinical trial for the treatment of renal carcinoma and lymphoma.…”
Section: Introductionmentioning
confidence: 99%